Comida at home - Ortigosa, Nuria (E|C, 2020)
94% of food delivery orders made in Spain are made from home. This implies that if we are ordering food that has already been prepared, we are not using our kitchens and that, therefore, our kitchens are today spread throughout the city and not necessarily in the same place. The packaging, the design of the food itself and our urban environment are being affected by the new routes that food generates, making new urban scenes visible. Likewise, the new social models of home occupation, as well as the advances and role that technology has acquired in society, are changing our domestic life. Should we still consider housing as a private space? Or on the contrary, are we transforming our homes into more diffuse houses and more related to public space?